Perceptions of preparedness: How hospital-based orientation can enhance the transition from academic to clinical learning. - Beavers, Lindsay; Christofilos, Voula; Duclos, Christinne; McMillen, Kelly; Sheehan, Jasmine; Tomat, Laura; Jeffs, Lianne; Kelsey, Rebecca; Bulmer, Beverly (Canadian Medical Education Journal, 2020)
Background: Clinical placements are essential for applied learning experiences in health professions education. Unfortunately, there is little consensus on how best to prepare learners for the transition between academic and clinical learning. We explored learners’ perceptions of hospital-based orientation and resulting preparedness for clinical placement. Methods: Sixty-three learners participated in a total of 18 semi-structured focus groups, during their clinical placements. Data were analyzed thematically. Results: We organized learners’ perceptions of hospital-based orientation that support their preparedness for placement into three themes: (1) adequate site orientation for learner acquisition of organization acumen and (2) clinical preceptor training to support unit/service and (3) individual components. Conclusion: Thoughtful attention to hospital-based orientation can support learners in transitioning from academic to clinical learning. Hospital organizations should attend to all three components during orientation to better support learners’ preparedness for clinical learning.